Imaging of Abnormal Air in the Abdomen and Pelvis - Sharma, Shobhit; McDougal, Jonathan; Pandey, Tarun; Jambhekar, Kedar; Ram, Roopa (Journal of Gastrointestinal and Abdominal Radiology, 2019)
The presence of abnormal air collection on an imaging study is quite often the reason as well as the solution to a diagnostic dilemma. The purpose of this review article is to develop an understanding of anatomical localization and determine etiology of abnormal air collections in the abdomen and pelvis. Abnormal air collections are commonly encountered on imaging studies on a daily basis, and this article will help familiarize the interpreting radiologist with the pathophysiology of these collections and help solve various diagnostic challenges and avoid potential pitfalls.
Keywords: air; pneumomediastinum; pneumoperitoneum; pneumothorax